2018
DOI: 10.1016/j.dib.2018.05.121
|View full text |Cite
|
Sign up to set email alerts
|

Dataset on the durability behavior of palm oil fuel ash self compacting concrete

Abstract: Datasets contained in this article are outcomes of the durability properties carried out on Palm Oil Fuel Ash (POFA) concrete specimens to determine the effect of acid attack, Sulphate resistance, water absorption and rapid chloride permeability. Specimens were immersed in 1% hydrochloric acid (H2SO4) solution, 5% sodium Sulphate for 28, 56 and 90 days and different exposure conditions. The dataset helps the readers to understand and evaluate the potential of POFA though a waste material can be used as a repla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 5 publications
2
6
0
Order By: Relevance
“…For both admixtures, the compressive strength increased with partial replacement and then decreased. Similar observations were also made by Ofuyatan and Edeki [25], Ranjbar et al [30] and Ofuyatan and Edeki [24] for SCC with palm oil fuel ash partial cement replacement and by Raisi et al [29] for rice husk ash partial cement replacement. The decrease in compressive strength is due to a weak interfacial transition zone, the porosity of the mortar during adhesion to the fine and coarse aggregates and the formation of cracks in the aggregates [13,32].…”
Section: Compressive Strengthsupporting
confidence: 84%
“…For both admixtures, the compressive strength increased with partial replacement and then decreased. Similar observations were also made by Ofuyatan and Edeki [25], Ranjbar et al [30] and Ofuyatan and Edeki [24] for SCC with palm oil fuel ash partial cement replacement and by Raisi et al [29] for rice husk ash partial cement replacement. The decrease in compressive strength is due to a weak interfacial transition zone, the porosity of the mortar during adhesion to the fine and coarse aggregates and the formation of cracks in the aggregates [13,32].…”
Section: Compressive Strengthsupporting
confidence: 84%
“…Rantung, Supit [2] observed a decrease in compressive strength in SSC with fly ash partial cement replacement. Similar observations was also made by Ofuyatan and Edeki [31], Ranjbar, Behnia [16] and Ofuyatan and Edeki [32] for SSC with palm oil fuel ash partial cement replacement and by Raisi, Amiri [15] for rice husk ash partial cement replacement.…”
Section: Compressive Strengthsupporting
confidence: 82%
“…Grdic et al [18] asserted that fly ash and hydraulic lime proved to be adequate in improving the strength and workability of concrete, which was also stated by Menninger [48]. On the other hand, Guneyisi et al [19] and Naik et al [6] worked on class F and class C fly ash, which showed an improved compressive strength, likewise the following substances: silica fume (Khaloo and Houseinian [20]); polypropylene fiber (Ray and Chattopadhyay [21]); palm oil fuel ash (Ofuyatan et al [49]); baggase ash (Sua-iam and Makul [23]); and metakaoline, microsillica and nanosillica (Barluenga et al [28]). It is recommended that future research focus on the addition of more than one type of agricultural waste to SCC production, as these wastes exhibit different pozzolanic properties.…”
Section: Discussionmentioning
confidence: 86%
“…The use of agricultural waste such as palm oil fuel ash (POFA), BA, and so on, as supplementary materials, has altered SCC workability. Hence, the use of this waste in SCC calls for caution, as higher percentages have also reduced the strength properties, according to Ofuyatan et al [49]. Interestingly, the durability properties have improved at a higher dosage.…”
Section: Discussionmentioning
confidence: 99%